An Introduction to Oral and Maxillofacial Surgery - Mitchell, D. A. David A. (Taylor&Francis, 2015)
An Introduction to Oral and Maxillofacial Surgery encompasses the full range of oral and maxillofacial surgery. It also addresses the necessary core competencies for undergraduates and those pursuing basic specialist training. The second edition now includes international perspectives. In the UK, oral and maxillofacial surgery is a unique discipline--the ninth of ten currently recognized surgical specialties--and trainees usually start from a dental qualification before gaining a medical one. In contrast, in Germany practitioners often start from a medical base and then obtain a dental degree while in North America they start from a dental base and may or may not become dually qualified. The books initial chapters cater to all approaches of initial training and crucially bring them together in the specialist surgical sections. In chapters where the UK, US, and German perspectives are distinctly different, a section at the end has been added offering a specific perspective. However, where there is general consensus the international views have been integrated into the main body of text. At the end of each chapter, where appropriate, readers will find relevant references and recommendations for further reading. This book can also be considered a definitive and consistently reliable source of information for those following the UKs Intercollegiate Surgical Curriculum.